Bilingual and monolingual students’ out-of-school learning environment in Turkey: A comparative study based on PISA 2018 data - Karamese , Cenan Isci (Asian Journal of Education and Training, 2023)
Students’ out-of-school learning environment is one of the most prominent factors affecting their school success, which is mostly a source of inequity unfavoring disadvantaged groups. In some countries including Turkey, bilingual students are among disadvantaged groups because most of them are from immigrant families with low socioeconomic status. PISA provides extensive data about students’ out-of-school learning environment to be analyzed. In this context, the purpose of this study is to compare monolingual and bilingual students’ out-of-school learning environment based on PISA 2018 data. The participants of this study are the PISA 2018 sample of Turkey including 6890 15-year-old students selected from 186 schools through stratified random sampling. PISA 2018 data were collected by PISA Student Questionnaire, which is an online data collection instrument. Results showed that there are meaningful differences between monolingual and bilingual students with respect to all variables representing their out-of-school learning environment with medium effect sizes. These findings indicate a possible inequity problem in the Turkish Education System with respect to out-of-school learning environments unfavoring bilingual students. To achieve a permanent solution, socio-economic inequities need system-wide reforms that are often difficult to execute. However, it is possible to reduce the negative effects of this problem by means of some precautions. In this regard, providing training for parents and increasing the accessibility of schools’ educational sources and technologies for disadvantaged students were suggested in this study.